Investigation of novel analytical tools and experimental methods for the development of intermediate temperature heat pipes - Werner, Thomas C. (2021)
Heat pipes have been a large part of the thermal management market for the past four decades and have contributed to the development and optimisation of countless components in the design of satellites, spaceships, formula racing cars, power plants and electronics cooling. These thermal management systems span a wide range of temperatures, which in turn, requires the heat pipe fluid to be specially selected to meet the application requirements. Recently, there has been an increasing demand for heat pipes which can operate in the 300°C to 600°C temperature range – a range which is still severely underdeveloped in the heat pipe marketplace due to the lack of conventional fluids which can adequately operate at these temperatures. This range is dubbed the ‘medium’ or ‘intermediate’ temperature range.